2010
DOI: 10.1177/0021998310376098
|View full text |Cite
|
Sign up to set email alerts
|

Composite materials obtained from textile fiber residue

Abstract: This article presents the use of fibers residue from textile industry to minimize environmental problems associated with material accumulation. Composite materials utilizing textile fiber residues and high density polyethylene were prepared. Effect of treatment with hot water on fibers to prepare composites was studied to provide an improvement in mechanical properties of these materials. This treatment on fibers was evaluated by X-ray diffraction and scanning electron microscopy techniques. Experimental resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In the case of fiber treated with hot water at 75ºC, an increase in the intensity of the cellulose peak can be observed, as its crystallinity index was the second heighest when compared to the untreated ("in natura") fibers. This result is in agreement with those obtained by Mulinari et al 21 who also observed that fibers from textile residues treated thermally at 100ºC were more crystalline than untreated fibers.…”
Section: Structural Characterization Of Fiberssupporting
confidence: 93%
See 3 more Smart Citations
“…In the case of fiber treated with hot water at 75ºC, an increase in the intensity of the cellulose peak can be observed, as its crystallinity index was the second heighest when compared to the untreated ("in natura") fibers. This result is in agreement with those obtained by Mulinari et al 21 who also observed that fibers from textile residues treated thermally at 100ºC were more crystalline than untreated fibers.…”
Section: Structural Characterization Of Fiberssupporting
confidence: 93%
“…However, the SEM analysis showed that defibrillation of the thermally treated fibers occurred with reduction of the fiber diameter (Figure 3d). Mulinari et al 21 also observed that the fibers from the textile residue were modified through a heat treatment at 100ºC, acquiring flattened forms. In addition, all the fibers presented pore size consistent with mesopore classification 35 .…”
Section: Surface Area Characterizationmentioning
confidence: 98%
See 2 more Smart Citations
“…Fiber-reinforced polymers are attractive because they are able to provide a beneficial balance between the traditional properties of a polymer (such as low part weight and ease of processability) and selective properties of metals (such as high strength, modulus, and toughness). 1 The low cost, ease of fabricating of complex parts, and isotropic nature are the attractive features leading to the selection of short fiber reinforced composites for large-scale production. 2 Among polymer matrix resins, aromatic polyimide, being widely applicable engineering plastics, exhibits numerous excellent properties such as high mechanical strength, high wear resistance, good thermal stability, high stability under vacuum, good anti-radiation as well as solvent resistance and so on.…”
Section: Introductionmentioning
confidence: 99%